Outdoor Sketching : Four Talks Given before the Art Institute of Chicago; The Scammon Lectures, 1914 - Smith, Francis Hopkinson, 1838-1915 (Salt Lake City, UT : Project Gutenberg, 2008)
"Outdoor Sketching" by Francis Hopkinson Smith is a collection of lectures on painting techniques delivered at the Art Institute of Chicago in the early 20th century. The book focuses on the practice and philosophy of outdoor painting, providing insights into the approach of sketching nature directly from observation rather than relying on studio work or memory. Through Smith's narrative, readers can expect to delve into the nuances of composition, mass, watercolors, and charcoal techniques, reflecting his personal experiences in developing a close relationship with the natural world. The beginning of "Outdoor Sketching" introduces the author$1 (Bs passion for painting outdoors, showcasing his belief that the spontaneous act of capturing nature's beauty is vital to the artist's craft. Smith discusses his lack of studio work, emphasizing the importance of executing pieces rapidly outdoors to maintain the essence and vibrancy of the landscape. He reflects on the unique joys of outdoor sketching, describing vivid scenes filled with dynamic color and life, while sharing practical tips on selection, composition, light, and mass that are essential for conveying the true spirit of the environment in art. (This is an automatically generated summary.)s
Composition -- Mass -- Water-colors -- Charcoal.
Release date is 2008-11-27
E-text prepared by Sankar Viswanathan, Juliet Sutherland, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Landscape painting; Landscape drawing